Electromagnetic turbulence in increased β plasmas in the Large Plasma Device. (9th August 2021) - Rossi, G.D.; Carter, T.A.; Seo, B.; Robertson, J.; Pueschel, M.J.; Terry, P.W.
Abstract : The variation of pressure-gradient-driven turbulence with plasma β (up to β ≈ 15 % ) is investigated in linear, magnetized plasma. The magnitude of magnetic fluctuations is observed to increase substantially with increasing β . More importantly, parallel magnetic fluctuations are observed to dominate at higher β values, with δ B_/ δ B_≈ 2 and δ B / B_0 ≈ 1 % . Parallel magnetic fluctuations are strongly correlated with density fluctuations and the two are observed to be out of phase. The relative magnitude of and cross-phase between density and parallel magnetic field fluctuations are consistent with the dynamic pressure balance (P+B_0^2/2μ _0 = constant ). A local slab model theory for electromagnetic, modified drift Alfvén waves, including parallel magnetic fluctuations, shows partial agreement with experimental observations.